An alternative approach for selecting TS vs. DS processes using the Nelson and Plosser time series - Αγιακλόγλου Χρήστος Ν. (SPOUDAI Journal of Economics and Business, 2001)
The initial study of Nelson and Plosser (1982) has been established in the literature as a point of reference and many research papers have worked on their data set trying to determine whether each U.S. series is generated by a trend stationary or by a difference stationary process. The objective of this paper is to re-examine the Nelson and Plosser data set using maximum likelihood estimation and to comment on the results based on the existing testing procedures. JEL Classification: C12, C22